2007
DOI: 10.1111/j.1365-2710.2007.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin, a cytochrome P450 3A inducer, decreases plasma concentrations of antipsychotic risperidone in healthy volunteers

Abstract: Rifampin when used concurrently with risperidone significantly decreases the plasma concentration of risperidone. Our results provide in vivo evidence of the involvement of CYP3A in the metabolism of risperidone, in addition to CYP2D6. Thus, co-administration of risperidone with CYP3A inducer(s), including rifampin should be recognized or avoided in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
1
26
0
Order By: Relevance
“…In particular, the function pathways coincided with previously reported rifampin-induced biological functions. For example, rifampin affected the hepatic drug disposition and metabolism [28, 29] and it was a potent inducer of drug-metabolizing enzymes [6, 2931]. Rifampin is also an inhibitor which rapidly downregulates angiogenesis and mitogenesis-related genes to target cancer cells [12, 32, 33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the function pathways coincided with previously reported rifampin-induced biological functions. For example, rifampin affected the hepatic drug disposition and metabolism [28, 29] and it was a potent inducer of drug-metabolizing enzymes [6, 2931]. Rifampin is also an inhibitor which rapidly downregulates angiogenesis and mitogenesis-related genes to target cancer cells [12, 32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the drug-metabolizing enzymes [6], transporters, and microRNAs (miRNAs) are regulated by rifampin [11, 12], and the mechanisms of the regulation of some of these genes are well-studied; however, little has been done to put the global gene expression effects of rifampin into biological pathways and interactive networks. Protein interaction network can depict and integrate information pertaining to domain architecture, post-translational modification, interaction networks and disease association for each protein in the human proteome [13].…”
Section: Introductionmentioning
confidence: 99%
“…CYP3A4 is abundant in human liver microsomes and plays an important role in the metabolism of many drugs, including anticancer drugs. Furthermore, CYP3A4 shows about five-to tenfold inter-patient variability [25][26][27] in the disposition of these drugs metabolic efficiency, and intra-patient variability is widely recognized for several major inducers [28,29] or inhibitors [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CYP3A4 by ketoconazole has been shown to result in increased plasma concentrations or decreased clearance of several atypical antipsychotics, including clozapine, quetiapine, ziprasidone, and risperidone [19][20][21]. Studies in healthy volunteers have shown that rifampin decreases plasma concentrations and increases clearance of risperidone [22,23], and there is evidence implicating rifampin in a clinically significant interaction with clozapine [24]. Such interactions may also be anticipated with quetiapine [20].…”
Section: Discussionmentioning
confidence: 99%